Memoria rota, tensión y armonía en crónicas mestizas novohispanas - Valeria Añón (Orbis Tertius, 2010)
The chronicles of the Conquest of Mexico display a particular tension between experience and knowledge as forms of validation of the narrative on the past. In these polemics, the recourse to memory [one's own and that of the ancestors] becomes a topic which is first stated by the chronicler and centuries later reassumed by the analyst. We here aim to show some of the uses of memory in chronicles of the mestizo tradition, in order to address the question regarding the textual configuration of the memorialist argument. As we approach these chronicles from the perspective of memory, we are again faced with the intermingling of conceptions and worldviews: besides the notions of "memorial", "memory" and "monument" in the Western tradition, we must consider the meanings of "memory" in the nahua world. We will devote the following pages to a brief analysis of these modulations